The ex vivo neurotoxic, myotoxic and cardiotoxic activity of cucurbituril-based macrocyclic drug delivery vehicles. Issue 6 (19th September 2014) - Oun, Rabbab; Floriano, Rafael S.; Isaacs, Lyle; Rowan, Edward G.; Wheate, Nial J.
Graphical Abstract: Abstract: The cucurbituril family of drug delivery vehicles have been examined for their tissue specific toxicity using ex vivo models. Cucurbit[6]uril (CB[6]), cucurbit[7]uril (CB[7]) and the linear cucurbituril-derivative Motor2 were examined for their neuro-, myo- and cardiotoxic activity and compared with β-cyclodextrin. The protective effect of drug encapsulation by CB[7] was also examined on the platinum-based anticancer drug cisplatin. The results show that none of the cucurbiturils have statistically measurable neurotoxicity as measured using mouse sciatic nerve compound action potential. Cucurbituril myotoxicity was measured by nerve-muscle force of contraction through chemical and electrical stimulation. Motor2 was found to display no myotoxicity, whereas both CB[6] and CB[7] showed myotoxic activity via a presynaptic effect. Finally, cardiotoxicity, which was measured by changes in the rate and force of right and left atria contraction, was observed for all three cucurbiturils. Free cisplatin displays neuro-, myo- and cardiotoxic activity, consistent with the side-effects seen in the clinic. Whilst CB[7] had no effect on the level of cisplatin's neurotoxic activity, drug encapsulation within the macrocycle had a marked reduction in both the drug's myo- and cardiotoxic activity. Overall the results are consistent with the relative lack of toxicity displayed by these macrocycles in whole animal acute systemic toxicity studies and indicate continued potential of cucurbiturils as drug delivery vehicles for the reduction of the side effects associated with platinum-based chemotherapy.